A Positioning System for Photodiode Device Using Collocated LEDs - Samer Said Saab; Khaled Kamal Saab (IEEE Photonics Journal, 2016)
This paper proposes a novel light-emitting diode (LED)-based system that can estimate the 3-D position of an object from the measurements of received signal strength (RSS). This work presents an alternative and relatively cheap approach for remotely estimating the location of an object. Unlike other LED-based positioning systems, the proposed method employs a single base station, including a few LEDs with different orientations. In addition, the proposed system does not require a ceiling on which the positioning LEDS are installed. To illustrate the performance capabilities of the proposed system, we support our scheme analytically and numerically.